2012
DOI: 10.1007/s13691-012-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

A hypervascular malignant solitary fibrous tumor in the mesentery of the rectum with good response to preoperative radiation therapy

Abstract: Solitary fibrous tumor (SFT) is an uncommon neoplasm located in the pelvis. Here, we report a case of hypervascular malignant SFT in the mesentery of the rectum that showed a significant response to preoperative radiotherapy. A 36-year-old man presented to our department with constipation and dysuria. Abdominal computed tomography confirmed a large round neoformation (155 mm in the longest diameter) with an evident contrastenhanced periphery and a central necrotic area in the pelvis. Considering the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…SFTs typically affect men and women equally and in middle ages 5 with no specific symptoms typically until the tumor starts to compress peripheral structures. 3 It is similar to our study in that the patient has no significant complaints except some discomforts in her abdomen and peri-anal region. Although, the CT scan showed the compressing signs of the tumor on the external anal sphincter.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…SFTs typically affect men and women equally and in middle ages 5 with no specific symptoms typically until the tumor starts to compress peripheral structures. 3 It is similar to our study in that the patient has no significant complaints except some discomforts in her abdomen and peri-anal region. Although, the CT scan showed the compressing signs of the tumor on the external anal sphincter.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we have also reported a rare case of grade II pelvic SFT. SFTs typically affect men and women equally and in middle ages 5 with no specific symptoms typically until the tumor starts to compress peripheral structures 3 . It is similar to our study in that the patient has no significant complaints except some discomforts in her abdomen and peri‐anal region.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent retrospective series demonstrated that 34% of all SFT occur in the abdominopelvic region and that the abdominopelvic cavity is a major primary site for SFT . However, a SFT that arises from the mesentery is unusual, and a SFT from the mesorectum is rarer still—we found only five reports describing such SFT .…”
Section: Discussionmentioning
confidence: 72%
“…A definitive preoperative diagnosis is important to differentiate SFT from other tumors because gastrointestinal stromal tumor can be treated with neoadjuvant chemotherapy. However, we resected this tumor without fine‐needle aspiration biopsy as it rarely provides enough tissue for a definitive diagnosis because of the heterogeneous distribution of cellular density within the tumor and because the tumor was considered to be resectable . We preoperatively planned a low anterior resection of the rectum but changed the procedure to tumor extirpation from the mesorectum because we judged the tumor could be resected without disturbing blood flow to the rectal wall.…”
Section: Discussionmentioning
confidence: 99%